2022
DOI: 10.1155/2022/6750317
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Trajectories for 16 Years and the Development of Left Ventricular Hypertrophy and Increased Left Atrial Size: The Korean Genome and Epidemiology Study

Abstract: Background. Elevated single blood pressure (BP) measurement can be associated with the development of hypertension-mediated target organ damage including left ventricular hypertrophy (LVH) and left atrial (LA) enlargement (LAE). However, long-term patterns of BP and their effects on LVH and LAE are poorly understood. We evaluated the association between the BP trajectories and the presence of LVH and LAE. Methods. We analyzed a total of 2,565 participants (1,267 males, 47.8 ± 6.7 years old) from the first bien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…22 Additionally, previous trials found that BP categories and their changes throughout lifetime based on repeated BP measurements and reflecting long-term exposure to normal or high BP are associated with measures of LV structure and function. 23,24 However, the results of this study 18 are obtained within the context of a well-conducted prospective observational study, are reliable and well presented.…”
Section: The Akershus Cardac Examination 1950 Study-strengths and Lim...mentioning
confidence: 63%
See 1 more Smart Citation
“…22 Additionally, previous trials found that BP categories and their changes throughout lifetime based on repeated BP measurements and reflecting long-term exposure to normal or high BP are associated with measures of LV structure and function. 23,24 However, the results of this study 18 are obtained within the context of a well-conducted prospective observational study, are reliable and well presented.…”
Section: The Akershus Cardac Examination 1950 Study-strengths and Lim...mentioning
confidence: 63%
“…Additionally, previous trials found that BP categories and their changes throughout lifetime based on repeated BP measurements and reflecting long‐term exposure to normal or high BP are associated with measures of LV structure and function 23,24 …”
Section: The Akershus Cardac Examination 1950 Study—strengths and Lim...mentioning
confidence: 99%